Carbon and nitrogen dynamics in a sandy groundwater-coupled ecosystem in the Monte Desert, indicated by plant stable isotopes - Aranibar, Julieta Nelida (2014)
The high productivity of sandy groundwater-coupled woodlands in the Monte Desert is exploited by local pastoralist communities for fuel, domestic use, and manure accumulation and export to irrigated oases. We explored processes and species that could replenish C and N losses from the ecosystem using stable isotopes of plants and nutrient analysis of soils. Foliar 15N natural abundances, which were lower in Prosopis flexuosa plants and C4 grasses from dune flanks, indicate that these plants may fix atmospheric N2. Groundwater availability did not decrease water use efficiency (indicated by similar foliar δ13C in dune flanks and interdune valleys), suggesting that the higher stomatal conductance allowed by the additional water source and reported in previous studies is coupled with higher photosynthetic rates, increasing productivity in interdune valleys. Water use efficiency and N stable isotopes of P. flexuosa responded to temporal changes in precipitations, suggesting rapid shifts of N sources, to uptake of recently mineralized soil N (higher δ15N and lower δ13C after rain events). Soil heterogeneity was low, except for ammonium and moisture in interdune valley soils. This study allows us to hypothesize that carbon is replenished in interdune valleys by increasing photosynthetic rates, and N is replenished by N2 fixation done by young P. flexuosa plants and grasses from dune flanks.